KNOWLEDGE MANAGEMENT SYSTEM AS MEANS OF MOBILIZATION OF COMPETITIVE ADVANTAGES OF THE INDUSTRIAL ENTERPRISE - K. B. Dobrova; N. V. Kirichenko (Модернизация, инновация, развитие, 2015)
The article stresses the importance and urgency of implementing knowledge management systems for aviation enterprises to enhance the competitive advantages of aircraft. Conservation promotes knowledge management system (SMZ), developed and approved by the national standard of the Russian Federation GOST R 53894-2010 «Knowledge Management. Terms and definitions». A formula for the calculation of some indicators of competitiveness.